2017
DOI: 10.1002/andp.201600342
|View full text |Cite
|
Sign up to set email alerts
|

Particle localization and hyperuniformity of polymer‐grafted nanoparticle materials

Abstract: The properties of materials largely reflect the degree and character of the localization of the molecules comprising them so that the study and characterization of particle localization has central significance in both fundamental science and material design. Soft materials are often comprised of deformable molecules and many of their unique properties derive from the distinct nature of particle localization. We study localization in a model material composed of soft particles, hard nanoparticles with grafted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 77 publications
(100 reference statements)
5
48
0
Order By: Relevance
“…We suggest that the transition between the power law scalings observed by Antonetti et al 12 for all different polymer architectures can be rationalized as the emergent dynamical heterogeneity that is characteristic of strongly interacting soft particle systems. 60 …”
Section: Resultsmentioning
confidence: 99%
“…We suggest that the transition between the power law scalings observed by Antonetti et al 12 for all different polymer architectures can be rationalized as the emergent dynamical heterogeneity that is characteristic of strongly interacting soft particle systems. 60 …”
Section: Resultsmentioning
confidence: 99%
“…102104 Similar trends have been observed in polymer-grafted nanoparticles having a moderate grafting density where this effect is especially large. 40 The dynamics of both polyelectrolyte stars having inter-mediate number of arms and moderately polymer-grafted nanoparticles show sharp slowing down with increasing concentration that is symptomatic of incipient solidification. Sciortino and coworkers 105 have recently shown that nanoparticles with a moderate number of grafted DNA chains can form an equilibrium amorphous state in which the crystalline state is metastable.…”
Section: Discussionmentioning
confidence: 99%
“…Stars having a moderate value of f can naturally be expected to behave as “soft” particles exhibiting significant fluctuations in size and shape as in case of flexible polymers. Simulation studies of other soft particle systems such as polymer-grafted nanoparticles 3840 have indicated a tendency to form equilibrium disordered solids rather than crystalline materials because of the fluctuating effect of the conformational disorder packing having low compressibility as in the case of crystals. We may then expect polyelectrolytes stars having an intermediate number of arms to form soft amorphous solid.…”
Section: Introductionmentioning
confidence: 99%
“…The hyperuniformity concept has brought new attention to the importance of quantifying the large-scale structural correlations in amorphous systems, regardless of whether they are hyperuniform. This has been borne out in recent studies concerning molecular jamming processes that underlie glass-formation in polymeric materials [76,79], and quantifying the large-scale structure of amorphous ices and transitions between their different forms [80]. Understanding structural and physical properties of a system as it approaches a hyperuniform state or whether near hyperuniformity is signaling crucial large-scale structural changes in a system will be shown to be fundamentally important and is expected to lead to new insights about condensed phases of matter.…”
Section: Disordered Hyperuniform Systems Are Distinguishable States Omentioning
confidence: 99%